Carbapenem-resistant bacteria in an intensive care unit during the coronavirus disease 2019 (COVID-19) pandemic: A multicenter before-and-after cross-sectional study. (16th April 2022) - Pascale, Renato; Bussini, Linda; Gaibani, Paolo; Bovo, Federica; Fornaro, Giacomo; Lombardo, Donatella; Ambretti, Simone; Pensalfine, Giulia; Appolloni, Lucia; Bartoletti, Michele; Tedeschi, Sara; Tumietto, Fabio; et al.
Abstract: Objective: To assess the incidence of colonization and infection with carbapenemase-producing Enterobacteriaceae (CPE) and carbapenem-resistant Acinetobacter baumannii (CR-Ab) in the ICUs of our city hospitals before and during the coronavirus disease 2019 (COVID-19) pandemic. Methods: We conducted a multicenter, before-and-after, cross-sectional study to compare the rates of colonization and infection with CPE and/or CR-Ab in 2 study periods, period 1 (January–April 2019) and period 2 (January–April 2020). Incidence rate ratios (IRRs) and 95% confidence intervals (CIs) of weekly colonization and infection rates for each period were compared for the 2 study periods using Poisson regression. Weekly trends in the incidence of colonization or infection for each study period were summarized using local weighted (Loess) regression. Results: We detected no significant change in either IRR and weekly trend in CPE colonization and infection during the 2 study periods. A shift from KPC to other CPE mechanisms (OXA-48 and VIM) was observed during period 2. Compared to period 1, during period 2 the IRR of colonization and infection with CR-Ab increased 7.5- and 5.5-fold, respectively. Genome sequencing showed that all CR-Ab strains belonged to the CC92/IC2 clonal lineage. Clinical strains clustered closely into a single monophyletic group in 1 of the 3 centers, whereas they segregated in 2 different clusters in the other 2 centers, which strongly indicates horizontal transmission. Conclusions: Our findings indicate the need to conduct infection control activities targeted against the spread of antimicrobial resistance between and within hospitals during the COVID-19 pandemic, and if necessary, remodulating them according to the new organizational structures imposed by the pandemic.